Immunogenicity and protective efficacy of Vibrio vulnificus flagellin protein FlaB in a wound infection model - YAMAZAKI, Kohei (J Vet Med Sci, 2017)
Vibrio vulnificus is known as an opportunistic bacterial pathogen that causes primary septicemia and wound infection in humans. Recently, the incidence of wound infection by V. vulnificus is increasing in warm countries. In this study, we examined a vaccine antigen against V. vulnificus in mice. FlaB, a component protein of the V. vulnificus flagellum, was expressed as a recombinant protein, named rFlaB. After immunization of mice with rFlaB, the mice were challenged by subcutaneous inoculation with V. vulnificus. Bacterial burdens in muscular tissue at the infection site in rFlaB-immunized mice were significantly decreased compared with those of control mice. We found that rFlaB immunization can partially suppress proliferation of V. vulnificus at the local infection site.